Efisiensi Pemasaran Lanting di Desa Karang Anyar Kecamatan Gedong Tataan Kabupaten Pesawaran - Real Irhamna; Marlinda Apriyani; Irmayani Noer (Journal of Food System & Agribusiness, 2021)
This study aims to analyze the marketing efficiency of lanting. The research method used is a survey method. This research was conducted in Karanganyar Village, Gedong Tataan Subdistrict, Pesawaran Regency, with 37 respondents. The analysis used is the marketing channel, marketing margins, business profits, and lanting marketing efficiency. The results of the analysis show that the most efficient marketing of lanting is a marketing channel that does not involve marketing agencies, namely producers directly to the end consumers. This marketing channel is the first channel (channel 1). Keywords: efficiency, lanting, and marketing